Fingerprint Privacy Protection Techniques: A Comparative Study - J S, Aafa; Salim, Soja (International Journal of Computer Sciences and Engineering, 2014)
Human fingerprints are rich in details called minutiae, which can be used as identification marks for fingerprint verification. But they are vulnerable to attacks and fake fingerprints can be generated to login into the system anonymously. With the widespread applications of fingerprint techniques in authentication systems, protecting the privacy of the fingerprint becomes an important issue. Therefore, in recent years, significant efforts have been put into developing specific protection techniques for fingerprint. This paper reviews some of the existing techniques which protect the privacy as well as security of the fingerprint systems.